Efforts to Improve Employee Creativity Through Transformational Leadership - Palupi, Majang (Universitas Muhammadiyah Yogyakarta, 2020)
This study aimed to examine the effect of transformational leadership on employee creativity. In this study, transformational leadership was seen from four dimensions: inspirational motivation, idealized influence, intellectual stimulation, and individual consideration. This study’s sampling technique was the purposive sampling technique by selecting Master program students who have worked. This study had distributed a total of 117 questionnaires, and the number of usable questionnaires was 100 employees. This study applied multiple regression to process the data. The results showed that the four transformational leadership dimensions, consisting of inspirational motivation, idealized influence, intellectual stimulation, and individual consideration, influenced employee creativity.